Use of proton pump inhibitors in dialysis unit in tertiary care hospital: a pharmaco-epidemiological study - Pendhari, Shabbir R.; Joshi, Kedar S.; Limaye, Ramchandra P. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Proton pump inhibitors (PPI) are generally thought to be safer drug with fewer adverse effects. Though this class of the drug is thought to be well tolerated, a detail study about actual use of these agents in nephrology department is still awaited in many parts of India. There had been case reports and case series which were reporting PPIs producing acute interstitial nephritis progressing to acute renal failure. The risk of PPI treatment in haemodialysis patients remains unexplored. The aim of the study was to evaluate a drug utilization of PPI in patient undergoing haemodialysis procedure. Methods: In this study every day visit to the dialysis units of the hospitals was carried out. After taking consent from the patients, the information from the case-report form was noted like; age, sex, diagnosis, laboratory reports and drug prescried. No personally identifiable information about patient or physician was collected. After this an interview of patients was taken. Results: In this study, out of 126 patients 76.6% were male and 23.4% were female. Out of these 126 patients 88.89% patients were on PPI. Nearly 54% were using PPI for more than six months. Nearly 29% patients were using PPI for more than 12 months. Conclusions: As many case-reports and studies are suggesting, there is co-relation of PPI and acute interstitial nephritis from this study we suggest that especially in nephrology unit patients’, more caution must be exercised while using PPI.